Congenital hypothyroidism due to ectopic sublingual thyroid gland in Prader-Willi Syndrome: a case report - Sarah Bocchini; Danilo Fintini; Graziano Grugni; Arianna Boiani; Alessio Convertino; Antonino Crinò (BMC, 2017)
Abstract Background Thyroid gland disorders are variably associated with Prader-Willi syndrome (PWS). Many of the clinical features in newborns with PWS are similar to those found in congenital hypothyroidism (CH). Case presentation We report a case of a girl with CH and PWS. At the age of 9 months CH caused by an ectopic sublingual thyroid was diagnosed, and hormone replacement therapy was started. In spite of this treatment a decrease in growth velocity, weight excess and delayed development were observed. At the age of 9 years PWS was suspected on the basis of phenotype and genetic tests confirmed a maternal uniparental disomy of chromosome 15. This is the second reported case of hypothyroidism due to an ectopic sublingual thyroid gland in PWS suggesting that, although rare, an association between CH and PWS may exist. In our case diagnosis of PWS was delayed because mental retardation, hypotonia, obesity and short stature were initially attributed to hypothyroidism. Conclusions In this context PWS should be considered in obese children with CH who do not improve adequately with l-thyroxine therapy. Also, thyroid function in all PWS children should be assessed regularly in order to avoid delayed diagnosis of hypothyroidism.